Voices and narratives in becoming a teacher (Encuentros, 2024)
In this text, the results of an investigative process are presented whose purpose was to reflect on the becoming of a teacher from the co-construction of 348 stories and 3 life stories of practicing teachers from the department of Antioquia-Colombia. One of the results obtained is the polyphony of voices that is generated from narrations, to from there, on the one hand, understand how it is that we constitute ourselves in the world and society and give meaning and meaning to the teaching profession; and on the other, as an approach to interpreting the world and reality from the qualitative method in educational research, where the biographical perspective, attentive listening and the collective reading of reconstructed texts allow, in their voice, the subject-teachers to express and narrate the configuration of becoming a master.
Keywords: becoming, teacher, identity, biographical-narrative approach, life stories, professional career.